SIMULATION OF THE CARDIOVASCULAR SYSTEM USING EQUIVALENT ELECTRONIC SYSTEM - Hassani, Kamran; Navidbakhsh, Mahdi; Rostami, Mostafa (Biomedical papers, 2006)
This paper describes simulation of the cardiovascular system using a complex electronic circuit. In this study we have taken a slightly different approach to the modeling of the system and tried to advance existing electrical models by increasing more segments and parameters. The model consists of 42 segments representing the arterial system. Anatomical and physiological data for circuit parameters have been extracted from medical articles and textbooks. The frequency of heart is 1 Hz and the system operates in steady state condition. Each artery is modeled by one capacitor, resistor and inductor. The left and right ventricles are modeled using AC power suppliers and diodes. The results of the simulation including pressure and volume graphs exhibit operation of the cardiovascular system under normal condition. The results of the simulation have been compared with the relevant experimental observation and are in good agreement with them.
Keywords: b Department of Mechanical Engineering; Iran University of Science and Technology; Tehran